2018
DOI: 10.1371/journal.pone.0194786
|View full text |Cite
|
Sign up to set email alerts
|

Impact of acute-phase complications and interventions on 6-month survival after stroke. A prospective observational study

Abstract: The outcome of stroke patients is complex and multidimensional. We evaluated the impact of acute-phase variables, including clinical state, complications, resource use and interventions, on 6-month survival after first-ever stroke, taking into account baseline conditions exerting a possible effect on outcome.As part of a National Research Program, we performed a prospective observational study of acute stroke patients in four Italian Regions. Consecutive patients admitted for a period of 3 months to the emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 50 publications
1
8
0
3
Order By: Relevance
“…We found that at any particular point in time, the hazard of death among adult stroke patients who had any of the neuro-medical stroke complications was seven times higher than those who had no complications, after adjusting for potential confounders. This finding was in line with the studies done in Italy, 25 Taiwan, 26 Saudi Arabia, 1 this can be explained by the effect of stroke-related depressed immunity; depressed gag-reflex, and delayed mobilization of admitted patients. Early management of complications along with early mobilization and rehabilitation of patients, could significantly lower the incidence of complications, shortens the length of hospital stay and disability after the onset of stroke symptoms.…”
Section: Discussionsupporting
confidence: 90%
“…We found that at any particular point in time, the hazard of death among adult stroke patients who had any of the neuro-medical stroke complications was seven times higher than those who had no complications, after adjusting for potential confounders. This finding was in line with the studies done in Italy, 25 Taiwan, 26 Saudi Arabia, 1 this can be explained by the effect of stroke-related depressed immunity; depressed gag-reflex, and delayed mobilization of admitted patients. Early management of complications along with early mobilization and rehabilitation of patients, could significantly lower the incidence of complications, shortens the length of hospital stay and disability after the onset of stroke symptoms.…”
Section: Discussionsupporting
confidence: 90%
“…worse survival among IS cases and older age and the first studied time cohorts (1986–1990 and 1997–2001) increased the likelihood of death in ICH cases. The data from prospective observational study of 1,030 stroke patients in four regions of Italy showed that predictors of increased mortality rates over six months controlling data by demographic factors, pre-stroke functions, underlying illnesses and risk factors were altered consciousness, hyperthermia, pneumonia, and heart failure, while antiplatelet therapy and early mobilisation significantly increased survival during 6 months after stroke [43]. Among SAH stroke events any of investigated variables were not associated with better or worse 1- and 5-year survival after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the fact that people who had a stroke controlled their blood pressure sufficiently well when using antihypertensive drugs [35]. According to other researchers, AH was also not a predictor of death for 6 months after the stroke that increased the chance of death for both total and ischemic stroke, although the frequency of AH among the dead within 6 months post-stroke subjects was significantly higher compared to survivors [43]. Similar results are confirmed by other researchers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data tersebut selaras dengan penelitian sebelumnya yang menyatakan bahwa pasien strok yang berada pada tingkat ketergantungan total dan parah masih menjadi kelompok pasien dengan jumlah terbanyak saat keluar rumah sakit dan tidak mengalami peningkatan yang signifikan. 18 Kemampuan AKS pada saat masuk rumah sakit dan selama menjalani rawat inap dapat memprediksi skor AKS atau outcome skor AKS pada saat keluar rumah sakit. Semakin tinggi tingkat ketergantungan AKS pada saat masuk rumah sakit, perubahan status tingkat ketergantungan AKS atau outcome skor AKS pada saat keluar rumah sakit tidak akan jauh berbeda.…”
Section: Pendahuluanunclassified